2020
DOI: 10.3390/microorganisms8050760
|View full text |Cite
|
Sign up to set email alerts
|

Donated Human Milk as a Determinant Factor for the Gut Bifidobacterial Ecology in Premature Babies

Abstract: Correct establishment of the gut microbiome is compromised in premature babies, with Bifidobacterium being one of the most affected genera. Prematurity often entails the inability to successfully breastfeed, therefore requiring the implementation of other feeding modes; breast milk expression from a donor mother is the recommended option when their own mother’s milk is not available. Some studies showed different gut microbial profiles in premature infants fed with breast milk and donor human milk, however, it… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

4
19
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
7
1

Relationship

4
4

Authors

Journals

citations
Cited by 15 publications
(23 citation statements)
references
References 37 publications
4
19
0
Order By: Relevance
“…This contrasts with the situation in adults where increased microbiota diversity is generally considered beneficial and associated with reduced disease risk [ 47 ]. However, our findings are in good agreement with other studies in which high bifidobacteria diversity has been reported in situations where the scenario for the gut microbiota development is not ideal [ 34 ].…”
Section: Discussionsupporting
confidence: 93%
See 2 more Smart Citations
“…This contrasts with the situation in adults where increased microbiota diversity is generally considered beneficial and associated with reduced disease risk [ 47 ]. However, our findings are in good agreement with other studies in which high bifidobacteria diversity has been reported in situations where the scenario for the gut microbiota development is not ideal [ 34 ].…”
Section: Discussionsupporting
confidence: 93%
“…The levels of total Bifidobacterium as well as those of the species B. bifidum , B. breve , B. catenulatum , B. dentium , B. longum , B. angulatum , B. animalis subsp. lactis , and B. adolescentis were determined by qPCR using the methods described elsewhere [ 25 , 34 ].…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…The absolute levels of relevant intestinal microbial groups ( Bacteroides - Prevotella - Porphyromonas group, Lactobacillus -group, Akkermansia , Clostridium cluster XIVa, Bifidobacterium and Faecalibacterium genera) as well as total bacteria were determined at 0 and 24 h of fermentation by qPCR using previously described primers and conditions ( Valdés et al, 2017 ). Variations in the levels of the species B. longum, B. bifidum , B. animalis , Bifidobacterium adolescentis and Bifidobacterium catenulatum were assessed as described elsewhere ( Salazar et al, 2015 ; Arboleya et al, 2020 ). In order to investigate microbial changes as regards to the basal microbiota, the data were expressed as the log-ratio of the Fold Change before (time 0) and after 24 h incubation with different probiotic strains.…”
Section: Methodsmentioning
confidence: 99%
“…However, this has provided limited knowledge on the impact of IAP at lower taxonomical levels. To overcome this limitation, developing next-generation techniques, such as the sequencing of the Internally Transcribed Spacer (ITS) within the rRNA locus [ 64 ], was useful as marker of Bifidobacterium species, as it has been demonstrated in studies focused on the vertical transmission of bifidobacteria [ 65 ], the effect of using donor and own-mother’s milk on the premature bifidobacterial community [ 66 ] or the impact of several perinatal factors on the establishment of Bifidobacterium species in premature and full-term babies [ 63 ].…”
Section: Introductionmentioning
confidence: 99%